2022
DOI: 10.1186/s13054-022-03958-6
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care-related loss of quality of life and autonomy at 6 months post-discharge: Does COVID-19 really make things worse?

Abstract: Objective To compare old patients hospitalized in ICU for respiratory distress due to COVID-19 with old patients hospitalized in ICU for a non-COVID-19-related reason in terms of autonomy and quality of life. Design Comparison of two prospective multi-centric studies. Setting This study was based on two prospective multi-centric studies, the Senior-COVID-Rea cohort (COVID-19-diagnosed ICU-admitted pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 34 publications
(31 reference statements)
0
22
0
Order By: Relevance
“…In univariate analysis, HEALTHY-MIND© VR system was associated with significant decrease in overall discomfort (median NRS = 4 [ 2 6 ]) before the session versus 2 [0–5] after the session, p = 0.02) . The two other specific relaxation techniques and the standard relaxation were not associated with significant changes (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In univariate analysis, HEALTHY-MIND© VR system was associated with significant decrease in overall discomfort (median NRS = 4 [ 2 6 ]) before the session versus 2 [0–5] after the session, p = 0.02) . The two other specific relaxation techniques and the standard relaxation were not associated with significant changes (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The consequences can be serious, from the development of an adrenergic stress response interfering with critical illness (tachycardia, polypnea, patient/ventilator asynchrony, agitation, immunosuppression, etc.) [ 3 , 4 ] to the development of a post-intensive care syndrome (PICS), including neuro-psychological disorders (anxiety, depression, post-traumatic stress syndrome) and chronic pain that delay the return to a social and professional normal life [ 5 , 6 ]. The link between suffering in ICU and the development of PICS has been highlighted for a long time [ 7 ], leading to conceptualize modern intensive care as the most humane possible [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether such a result was mainly due to COVID-19 per se or to the related hospitalization cannot be inferred from our data. However, a recent and interesting study showed that, compared with patients requiring a stay in the intensive care unit, people infected with COVID-19 were less likely to suffer from a loss of usual activities [ 3 ]. Thus, rather than COVID-19 alone, hospitalization appears to be an important cause of the loss of autonomy in patients infected with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…As the SARS-CoV-2 pandemic has spread throughout the world, research has allowed us to increase our knowledge of this virus and to optimize COVID-19 infection prevention and treatment [ 1 ]. However, to date, studies concerning the nutritional status of patients after a COVID-19 hospitalization, in the long term, are relatively few and those concerning their autonomy are even fewer [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation